In-water resisted swim training for age-group swimmers: An evaluation of training effects - Kojima, K.; Brammer, C. L.; Sossong, T. D.; Abe, T.; Stager, J. M. (Pediatric Exercise Science, 2018)
Purpose: The purpose of this study is to compare the efficacy of resisted sprint swim training with that of nonresisted sprint swim training on 50-m freestyle competition time (Vmax50) in age-group swimmers. Methods: Twenty-four age-group swimmers (age 10.6-14.9 y) were divided into resisted or nonresisted sprint swim training groups and completed a sprint swim training intervention 2 times per week for 10 weeks. Repeated 10-m sprints with progressively increasing resistance were used to determine measures of swim power. Skeletal muscle mass was estimated using B-mode ultrasound. Maturity status was estimated using predicted adult height (%Htadult) and maturity offset. Results: A 2-way repeated-measures analysis of variance revealed no group×time interaction for measured variables. Vmax50 was correlated with skeletal muscle mass and swim power variables, but no significant relationship was found between relative changes in these variables. Estimated maturity status (%Htadult) appeared to be associated with initial measures of swim power and performance variables. Conclusions: Ten weeks of resisted sprint swim training was not any more effective than nonresisted sprint swim training at improving sprint swim performance in age-group swimmers.